Collaborative Stakeholder Networks in Elderly Welfare Program Implementation: A Social Network Analysis of the ROSELA Program in Lamongan Regency, Indonesia - Bagus Surya Dwitama; Mochammad Rozikin; Moh. Said (MASI Mandiri Edukasi, 2026)
Local governments in Indonesia increasingly rely on multi-actor collaboration to deliver targeted social assistance to vulnerable groups, including the elderly poor. This study examines the stakeholder network underlying the Elderly Welfare Program (Program Sejahtera Lansia, ROSELA) implemented by the Social Affairs Office of Lamongan Regency, which provides a food-assistance cash transfer of Rp900,000 per beneficiary family (Keluarga Penerima Manfaat, KPM) every three months, reaching 80 KPM across eight sub-districts (kelurahan) in Lamongan District by fiscal year 2026. Using a descriptive qualitative case-study design, primary data were collected through in-depth interviews and field observation of purposively selected informants, complemented by secondary data from technical operational guidelines and integrated social welfare records. Data were analysed using Creswell's qualitative analysis procedure and interpreted through three complementary frameworks: Social Network Analysis (SNA), the policy implementation model of Van Meter and Van Horn, and Van Waarden's seven dimensions of policy networks. Findings show that the ROSELA network is complex and multi-actor, with the Social Affairs Office occupying a central hub position; high density at the operational level but low density across sectors; an isolated cluster of unregistered elderly; and the strongest triadic closure among the village head, social assistance officer, and food-catering provider. Policy standards are clear at the output level but not the outcome level; financial resources are adequate through partnership with a regional bank, but human resources and legal grounding remain weak. The network is best characterised as a centralised, hierarchical, directive network at a moderate level of institutionalisation, with uneven power distribution favouring government actors over beneficiaries. The study concludes that ROSELA is operationally effective but institutionally fragile, and recommends a permanent legal framework, cross-sectoral integration, and formal participation channels for beneficiaries.